Learning together program for reading and writing interest in Arahan Kidul Village - Rahmawati, Eka; Hadi Senen, Syamsul (Universitas Pendidikan Indonesia, 2023)
Reading and writing literacy is the main ability that students must master, because reading and writing can greatly impact the quality of human life. Arahan sub-district, Arahan Kidul village is one of the places where the Indonesian Education University's Thematic Real Work Lecture (KKN-T) program is held for one month. It is known that there is still little attention paid to interest in reading and writing in the Arahan Village, therefore, in KKN-T activities, there is a joint learning work program which is expected to help students to be more active in learning to read and write. In this article, we will discuss the initial stages of activities and the implementation stages of the joint learning program. This article uses a descriptive method with a qualitative approach by collecting data obtained from observations and short interviews with students. The results found from this research were that students' lack of interest in reading and writing was due to a lack of supporting facilities and infrastructure. Meanwhile, students' motivation to learn to read and write is classified as very high. The impact resulting from this KKN-T activity is that human resources are facilitated to help guide students in learning to read and write so that students' enthusiasm is awakened to be more active in learning to read and write independently. Future recommendations hope the village and school can provide innovation and special learning media for elementary school students in Arahan Kidul.